Design and Validation of Teaching Modules for the Merdeka Curriculum Based on Local Wisdom to Instil Character Values - Salmia, Salmia; Nursalam, Nursalam; Bancong, Hartono (PPSDP International Journal of Education, 2024)
This study aims to design and validate teaching modules for the Merdeka Curriculum based on local wisdom to instill local wisdom values. These modules are designed to provide practical guidance for educators to integrate local values into the learning process, thereby enhancing students’ character education. The research method employed is a research and development approach, involving systematic stages from needs analysis to module validation. Data were collected through various methods, including questionnaires, interviews, observations, and documentation. Data analysis was conducted using the Aiken’s V validity test. The validation results by experts indicated that the developed teaching modules have a high level of validity. This research has significant implications for improving education quality and fostering appreciation for cultural diversity. Additionally, it contributes to understanding the effectiveness of a local wisdom-based approach in character education.